VIETNAMESE LABOR EXPORT TO JAPAN DURING THE PERIOD 1992–2023: A “PUSH”–“PULL” THEORY PERSPECTIVE - Thuy Linh, Nguyen; Thanh Truc, Le (HNUE Journal of Science: Journal of Social Sciences, 2026)
Drawing on the “push” - “pull” theoretical framework and employing historical analysis in combination with statistical analysis and field-based surveys, this article seeks to elucidate the key factors driving Vietnamese workers to choose Japan as a destination during the period 1992–2023. The study aims to explain migration decisions as shaped simultaneously by domestic “push” factors and Japan’s “pull” factors, thereby reflecting the structural compatibility between labor supply in Vietnam and labor demand in Japan. On this basis, the article provides an overview of the patterns and characteristics of Vietnamese labor migration to Japan and examines its economic, social, and foreign policy implications. In doing so, the study contributes to a more comprehensive assessment of the role of labor export in Vietnam’s post-Đổi mới reform and international integration process.